Distributed-memory concepts in the wave model WAVEWATCH III - Tolman, Hendrik L (Parallel computing, 2002)
Parallel concepts for spectral wind-wave models are discussed, with a focus on the WAVEWATCH III model which runs in a routine operational mode at NOAA/NCEP. After a brief description of relevant aspects of wave models, basic parallelization concepts are discussed. It is argued that a method including data transposes is more suitable for this model than conventional domain decomposition techniques. Details of the implementation, including specific buffering techniques for the data to be communicated between processors, are discussed. Extensive timing results are presented for up to 450 processors on an IBM RS6000 SP. The resulting model is shown to exhibit excellent parallel behavior for a large range of numbers of processors.